About the affine normal of a hypersurface in connected space - Berezman, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. М. Березман. Об аффинной нормали поверхности в пространстве со связностью A. Berezmanas. Apie hiperpaviršiaus afininę normalę afininio sąryšio erdvėje